Analysis of the Ability of Field Dependent and Field Independent Learning Styles in Biology Problem Solving - Reskywanti, Reskywanti; Jamhari, Mohammad; Ratman, Ratman; Tangge, Lilies; Afadil, Afadil; Azzajjad, Muhammad Fath (EDUKASI, 2023)
One of the impacts of the Teacher Center Learning (CTL) learning model in the classroom is that students' thinking creativity is less developed and students ability to solve problems is low. This study aims to analyze the problem-solving ability of Animal Ecology Biology Education students based on field-dependent and field-independent cognitive styles. This research is a descriptive study using a qualitative approach. The subjects of this study were Biology Education students in the sixth semester (VI) who programmed animal ecology courses totaling 24 people. The research instrument was the Group Embedded Figure Test (GEFT) which amounted to 25 points. Problem-solving questions in the form of descriptions of 4 numbers and interview guidelines. Based on the results showed that the problem-solving ability of students with field-independent cognitive style is better than field dependent because students with field-independent cognitive style are able to separate themselves from their environment while students with field-dependent cognitive style are still influenced by the surrounding environment.